Metabolic Syndrome and Suicidal Ideation in Korean Based on the 2010 Korean National Health and Nutrition Examination Survey - Kim, Sun-Mi (Korean Neuropsychiatric Association, 2014)
The aim of this study was to investigate the relationship between metabolic syndrome and suicidal ideation in Korean. This study was based on the 2010 Korean National Health and Nutrition Examination Survey. A questionnaire was used to measure suicidal ideation and physical examination was performed to measure waist circumference, blood pressure, fasting glucose, cholesterol and triglyceride levels. Complex samples logistic regression was performed to estimate the relationship between metabolic syndrome and suicidal ideation among adults and adolescents. Subjects with metabolic syndrome were more likely to have suicidal ideation in adult. There would be essential needs to evaluate suicidal ideation in adult with metabolic syndrome and to follow up suicidal ideation in adolescents with metabolic syndrome.